Mechanical Performance Evaluation of Al2O3–ZrO2–Ti Composite Materials - Nur Aziera, Nur Aziera; Mebrahitom, A.; Azmir, Azhari; Saptaji, Kushendarsyah (Springer Singapore, 2023)
The applications of ceramic based materials is becoming a trend due to their important mechanical and microstructural properties. This work evaluates the mechanical properties of ceramics composite of Al2O3–ZrO2 reinforced with Titanium (Ti) particles. The material is known for the application of biomedical devices due to the optimized functional properties. The mechanical properties of Al2O3–ZrO2 composites can be enhanced by incorporating Ti. To measure the mechanical properties, standard size samples of the ceramic composites were fabricated through powder processing method to consolidate the powders. A varying composition of Ti ranging from 5–45% by volume was used. Then, the measurements were conducted on each sample to determine the physical and mechanical performance of the composite. As a result, the newly produced composite materials with 75 vol.% Al2O3 + 10 vol.% ZrO2 + 15 vol.% Ti showed better physical and mechanical properties than the other compositions based on the requirements in the biomedical applications.